Max Aguilera-Hellweg, Photography from surgery to robotics - Jessica Ragazzini (Angles)
Anthropomorphic robotics have become increasingly familiar in our daily lives. Photographer and surgeon Max Aguilera-Hellweg moved from projects focusing on human bodies undergoing surgery to photographs of androids and their inner architecture. Why did the photographer choose to give up the human body to turn to its simulacrum? What does the robot have that the human body doesn’t have? What is the point of photographing objects that resemble human beings? These are the questions that will guide our analysis of the work of Max Aguilera-Hellweg.